2016
DOI: 10.1371/journal.pone.0164434
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Exposure to Zinc Oxide Nanoparticles on Development, Zinc Metabolism and Biodistribution of Minerals (Zn, Fe, Cu, Mn) in Mice

Abstract: Zinc oxide nanoparticles (nano-ZnOs) are widely used and possess great potentials in agriculture and biomedicine. It is inevitable for human exposure to these nanoparticles. However, no study had been conducted to investigate the long term effects of nano-ZnOs. This study aimed at investigating effects of nano-ZnOs on development, zinc metabolism and biodistribution of minerals (Zn, Fe, Cu, and Mn) in mice from week 3 to 35. After the characteristics of nano-ZnOs were determined, they were added into the basal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 58 publications
8
64
0
Order By: Relevance
“…Dietary supplemented 450 mg kg −1 nano‐ZnOs and 3000 mg kg −1 ZnO may downregulate the uptake of Zn at higher dosages to prevent toxicity. Wang et al . reported that Zn bioavailability decreased with increasing dietary nano‐ZnOs concentration due to the significantly increased fecal Zn concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary supplemented 450 mg kg −1 nano‐ZnOs and 3000 mg kg −1 ZnO may downregulate the uptake of Zn at higher dosages to prevent toxicity. Wang et al . reported that Zn bioavailability decreased with increasing dietary nano‐ZnOs concentration due to the significantly increased fecal Zn concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The novel properties of nanoparticles include small size, large specific surface area, high surface activity, more surface active centers, and high catalytic efficiency . Zinc oxide nanoparticles (nano‐ZnOs) are widely used and possess excellent potential in agriculture and biomedicine . Zinc oxide nanoparticles exhibit effective antimicrobial activity against E. coli and Staphylococcus aureus in vitro , which indicates that nano‐ZnOs may work as a potential alternative product for pig feeding and may contribute to lower zinc excretion in animal wastes .…”
Section: Introductionmentioning
confidence: 99%
“…The micronutrient of Zn was essential for the development of tissues in the body, which was absorbed by the intestinal epithelial cells, transported in blood and finally accumulated in tissues such as pancreas (Wang, Lu et al, 2016). Zinc is involved in the biological processes of pancreas including the secretion of digestive enzymes as well as regulating Zn secretion (Kelleher, McCormick, Velasquez, & Lopez, 2011 to 20,000 mg/kg caused lesions in the pancreas of chicks (Dewar, Wight, Pearson, & Gentle, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…All pigs were slaughtered via electrical stunning. Samples to determine mineral concentrations and mRNA expression were collected as described by Wang et al (2016). Briefly, lungs, heart, kidney, liver, and longissimus dorsi muscle (LDM) were collected and stored at -20 °C to determine mineral concentration.…”
Section: Methodsmentioning
confidence: 99%